BENZYLIDENE CYCLOPENTANONE DERIVATIVES AS INHIBITORS OF RAT LIVER GLUTATHIONE S-TRANSFERASE ACTIVITIES - Sudibyo Martono (Indonesian Journal of Chemistry, 2005)
The effect of the curcumin analogues, 2,6-bis-(4-hydroxy-3-methoxy benzylidene) cyclopentanone (B1) and two of its derivatives on m class glutathione S-transferases (GSTs) from phenobarbital-induced and uninduced rat liver cytosol has been studied to elucidate their anti-inflammatory activity. GST activity was monitored spectrophotometrically using 1,2-dichloro-4-nitrobenzene. B1 was the most potent inhibitor of GSTs, both in uninduced and in phenobarbital-induced rat liver cytosol. These inhibitory properties might be explained as part of the anti-inflammatory activity of benzylidene cyclopentanone derivatives (B1 and B12).